The ballad of Pemi Tshewang Tashi : a wind borne feather / (Acc: 1288) a wind borne feather - Karma Ura, 1928-; Bhutan. Ministry of Planning (Thimphu : Ministry of Planning : Distributors, Pekhang Enterprise : DSB Enterprisess, 1996)
English translation of Bhutanese folk tale.
Keywords: Tales; Folklore